Cyber-Based Human Trafficking for Sexual Exploitation: An Islamic Law Perspective - Mamduh Hilmi; Muhammad Azkia Fahmi (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2026)
Abstract: This article examines the emergence of human trafficking based on cyber sexual exploitation as a contemporary form of human trafficking operating through cyberspace, resulting in legal vacuums and regulatory ambiguity. This study aims to identify various forms of online sexual exploitation trafficking and to examine Islamic legal perspectives on appropriate criminal sanctions for such acts. The method used is normative juridical with a conceptual approach, grounded in secondary data collected systematically through literature review. The collected data are then qualitatively analysed through processes of decomposition, interpretation, and evaluation of the legal materials examined. The findings reveal that although online sexual exploitation trafficking is not explicitly recognised in classical fiqh literature, the essence of the act is substantively contrary to the principles of maqashid sharia. Within the framework of Islamic legal classification, this crime is categorised as a jarimah ta'zir, in which the determination of sanctions is left to the authority of the state or a judge. The novelty of this research lies in the effort to integrate classical Islamic legal concepts with modern cyber legal mechanisms. This approach has not been systematically studied in the context of digital-based human trafficking. The contribution of this research is to provide a normative and moral framework as a basis for developing both Islamic and national legal policies to address increasingly sophisticated cybercrimes, while strengthening the ethical foundations for protecting human dignity and honour in the digital age.